PRINCIPLES OF IMPLEMENTATION OF CURRENT PROTECTION FROM INTERPHASE SHORT-CIRCUITS ON THE POWER LINES WITH UNILATERAL FEED - F. A. Romaniuk; M. A. Shevaldin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The article describes the implementation of the principle of overcurrent protection from interphase  short-circuits  on  the  power  lines  with  unilateral  feed.  The  expression  of  the detection of the fault location by the relative value of the distance from the installation of pro- tection to the point of damage with the help of the results of operational control of the short- circuit current damaged phases has been suggested in the article. Also the expression for determining  the  time  delay response  for  such  protection  has been  presented,  taking  into account fault location that had been detected.The paper proposes and describes the functional diagram of the overcurrent protection in detail, provides realization of the implementation of the principles set out in the article. Paper content includes the description of the elements of the considered overcurrent protection, such as input current transducers connected to the measuring current transformers of the protected line, maxiselector, miniselector, block of the determination of the mode type, the measuring unit with the setting unit, detecting fault location unit with the setting unit, calculation unit and control unit with time delay parameter setting, an OR gate, the actuating element, that opens circuit breaker of the protected line. The operation of the proposed scheme is reviewed in  the  article.  All  units  and  elements  of functional  circuit overcurrent protection  can  be implemented with the help of analog and digital technology. Modern microprocessors can be used for these purposes.The efficiency of provided implementation of the principles of overcurrent protection from phase-to-phase short circuits on the power lines with unilateral feed was studied by computational experiments. These results confirm the effectiveness of the proposed solutions and also trip of short-circuit within the main zone line protection is provided without delay, and in the end zone redundancy – with time delay that is not exceeding 2Δt in all  areas, including the head portion of the network.